2012
DOI: 10.1007/s00192-011-1645-3
|View full text |Cite
|
Sign up to set email alerts
|

The results of a 24-h pad test in Brazilian women

Abstract: The value of the 24-h pad test established by the ICS was not valid for the investigated sample. Environmental conditions, menopausal status, and use of hormone therapy can interfere with the values of the pad test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The upper limit of weight increase for the 1‐hr test in continent women is 1.4 g (equivalent to 1.4 ml) and 1.3–4.4 g for 24‐hr test. These values may increase in situations of increased perspiration . In the analysis of 1‐hr pad test, an increase of 1–10 g is classified as representing mild incontinence, 11–50 g moderate and >50 g severe incontinence.…”
Section: Resultsmentioning
confidence: 99%
“…The upper limit of weight increase for the 1‐hr test in continent women is 1.4 g (equivalent to 1.4 ml) and 1.3–4.4 g for 24‐hr test. These values may increase in situations of increased perspiration . In the analysis of 1‐hr pad test, an increase of 1–10 g is classified as representing mild incontinence, 11–50 g moderate and >50 g severe incontinence.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is very difficult to control for the presence of sweat and vaginal secretions, which are highly variable and depend on factors such as weight, activity levels, environmental conditions, and sexual arousal. 6,7 The ICS defined upper limits of weight increase for a 1h pad test for a continent woman is 1.4 g (equivalent to 1.4 ml) and for a 24-h pad test are 1.3-4.4 g (equivalent to 1.3-4.4 ml). 5 UI is divided into mild (1-10 g), medium (1-50 g) and severe (>50 g) based on 1-h PWGs or mild (4-20 g), moderate (21-74 g), and severe (>75 g) based on 24-h pad weights.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Brazil showed that pad weights are affected by temperature and humidity, which can increase perspiration. 16 Given the amount of prior incontinence experienced by fistula patients, higher thresholds for pad tests (either 1.5 or 2.0 g) may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%